2020
DOI: 10.1039/d0dt03771k
|View full text |Cite
|
Sign up to set email alerts
|

A valence tautomeric cobalt–dioxolene complex with an anchoring group for prospective chemical grafting to metal oxides

Abstract: Here we synthesized a valence tautomeric cobalt-dioxolene complex featuring a protected anchoring group. At room temperature, the complex reveals a nearly pure low-spin-Co(III)-catecholate state in the solid state, but a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…The assignment of the transitions (Table S5) using TDA-DFT confirm the identity of the characteristic tautomeric bands for the [Co(dbdiox)-(dbsq)(N 2 L)] family. 23,32,66 Density Functional Theory Calculations. A pioneering DFT study on the VT complex [Co(dbdiox)(dbsq)(phen)] was reported by Noodleman, Hendrickson et al in 1997.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The assignment of the transitions (Table S5) using TDA-DFT confirm the identity of the characteristic tautomeric bands for the [Co(dbdiox)-(dbsq)(N 2 L)] family. 23,32,66 Density Functional Theory Calculations. A pioneering DFT study on the VT complex [Co(dbdiox)(dbsq)(phen)] was reported by Noodleman, Hendrickson et al in 1997.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These changes confirm hs -Co II (SQ • ) 2 → ls -Co III (SQ • )­(Cat) switching and thus the CIVT effect . The band in the SWIR region is assigned to the ligand-to-ligand intervalence charge transfer (LLIVCT) transition, which is a spectroscopic signature of the ls -Co III (SQ • )­(Cat) state in complexes featuring two dioxolene ligands in different oxidation levels. ,, The evolution of absorption at 750 nm has been analyzed with our revised model (see the Experimental Section and Figure S2) yielding the association constant K a = 5.7(5) × 10 3 L mol –1 for stypy binding to 1 *HS , which is in excellent agreement with the previously obtained data (4(1)–6(2) × 10 3 L mol –1 ) …”
Section: Results and Discussionmentioning
confidence: 87%
“…111 Similarly, in the complex [Co(BzOEt-phen)(t-Budiox) 2 ] (41; BzOEt-phen = ethyl 4-(1-10-phenanthrolin-5-yl)benzoate), T c shifts from 261-265 K to 230-231 K upon moving from DCM to toluene. 112 It is important to note that for several of these examples, solution-state equilibria were investigated in only two or three solvents. More detailed solvatochromic analyses can often be precluded by insolubility or dissociation/decomposition in certain solvents.…”
Section: Solvatochromism and Redox Isomerism: Valence Tautomerismmentioning
confidence: 99%